Pengaruh Kualitas Pelayanan, Harga dan Promosi terhadap Keputusan Pembelian Produk Tupperware di Semarang - Aminah, Aniafatul; Widowati, Maduretno (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aims to determine the effect of service quality, price and promotion on purchasing decisions for Tupperware products in Semarang. This type of research uses a quantitative approach. The population in this study are consumers who buy Tupperware products in Semarang. The sample used was as much as 100 respondents, using a probability sampling technique with the method of collecting data by distributing questionnaires online. The method of analysis in this study is multiple linear regression analysis. Data management uses SPSS 21 For Windows software. The results showed that partially Service Quality had a positive and significant effect on Purchasing Decisions. Price has a positive and significant effect on purchasing decisions. Promotion has a negative and insignificant effect on purchasing decisions. While simultaneously or together Service Quality, Price and Promotion have a positive and significant effect on Purchase Decision. Keywords: Service Quality, Price, Promotion, Purchase Decision